The Naxalites and their ideology - Ray, Rabindra (New Delhi ; Oxford : Oxford University Press, 2011)
This text describes the history of the development of the Naxalite movement, from its origins in the split of the communist movement in India to the death of Charu Mazundar - its founder - in 1972.
Previous ed.: 2002.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Naxalite movement -- History